Nalar Filosofis Sustainable Development Goals (SDGS) dalam Tata Kelola Filantropi Islam Berbasis Masjid di Surabaya - Imron Mustofa (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2021)
This article examines the governance of Islamic philanthropy as an economic movement for the people based on the Surabaya al-Akbar Mosque. It is undeniable that the fulfilment of community needs cannot be separated from the completion of their financial requirements. Al-Akbar Mosque has excellent potential as an implementation of Islamic values in fulfilling the Sustainable Development Goals. Armed with a philosophical analysis approach, this article focuses on studying the philosophical foundations in the performance and governance of Islamic philanthropic funds at the Al-Akbar Mosque. This study found several findings: The paradigm of economic development based on the Al-Akbar mosque appears to have expanded its meaning from the point of view of the conventional economy. In addition, Islamic philanthropy funds are managed based on the distribution of ratios between mosque sectors: tarbiyah, secretariat, ri'āyah and imārah.